The History of Assimilation of the Polish Diaspora in France in the 20th Century (Selected Issues) - Pachowicz, Anna (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
The aim of this article is to characterise the Polish Diaspora in France in the 20th century (including its structure and assimilation processes). In the history of the Polish State, there were many periods when Poles, for various complex reasons, decided to migrate to France. Poles were most often motivated to migrate by economic and political problems (Poles did not have their own state until 1918). On the other hand, the difficult economic and demographic situation of France at the beginning of the 20th century after the Great War encouraged immigrants from various countries (Spain and Italy), including Poland as well. The history of Polish migration to France can be divided into several different periods occurring over different centuries. Each of them was characterised by different motives, numbers, socio-professional features, expected length of stay on the Seine, and consequently resulted in differentiated assimilation into French society.